2013
DOI: 10.1002/lary.24235
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear pharmacokinetics of cisplatin: An in vivo study in the guinea pig

Abstract: Objectives/Hypothesis: Cisplatin produces toxic lesions to outer hair cells (OHCs) in the cochlear base but not in the apex. The objective of this study was to compare the pharmacokinetic profile of cisplatin in scala tympani (ST) perilymph in the cochlear base and apex, respectively.Study Design: In vivo animal study. Methods: Forty-seven guinea pigs were given an intravenous bolus injection of an ototoxic dose of cisplatin. Ten to 240 minutes after cisplatin was given, blood, cerebrospinal fluid (CSF), and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…Cisplatin pharmacokinetics in the inner ear after intravenous injection is influenced by its strong binding to the plasma proteins rendering a large part of it nonactive and by the barrier systems in the cochlea, the blood-perilymph barrier, separating blood from perilymph, and the intrastrial fluid-blood barrier, separating blood from endolymph [15]. The amount of free chemotherapeutic agent reaching targets in the cochlea is responsible for the ototoxic effect and consequent hearing loss.…”
Section: Resultsmentioning
confidence: 99%
“…Cisplatin pharmacokinetics in the inner ear after intravenous injection is influenced by its strong binding to the plasma proteins rendering a large part of it nonactive and by the barrier systems in the cochlea, the blood-perilymph barrier, separating blood from perilymph, and the intrastrial fluid-blood barrier, separating blood from endolymph [15]. The amount of free chemotherapeutic agent reaching targets in the cochlea is responsible for the ototoxic effect and consequent hearing loss.…”
Section: Resultsmentioning
confidence: 99%
“…They found that in samples of scala tympani aspirated from the basal turn in guinea pigs, the concentration of cisplatin peaked within half an hour after a 3-min intravenous infusion of cisplatin (Hellberg et al 2009(Hellberg et al , 2013. With a cisplatin dose of 8 mg/kg body weight, the maximum concentration of cisplatin in scala tympani from the basal turn was approximately 6 μM (Hellberg et al 2013 ). Compared to blood, cisplatin showed a delayed elimination from scala tympani perilymph within the fi rst hours after administration (Hellberg et al 2009(Hellberg et al , 2013, after which the concentration of cisplatin was below the level of detection (Hellberg et al 2013 ).…”
Section: Inner Ear Pharmacokineticsmentioning
confidence: 95%
“…A third consideration is that only tiny volumes can be sampled from the inner ear due to the small dimension of the inner ear compartments and the risk of contamination of the samples with cerebrospinal fl uid (Hara et al 1989 ;Salt et al 2006 ). Ehrsson and coworkers performed pharmacokinetic studies using a liquid chromatographic technique for the selective analysis of intact cisplatin in perilymph samples from experimental animals treated with cisplatin (Hellberg et al 2009(Hellberg et al , 2013. They found that in samples of scala tympani aspirated from the basal turn in guinea pigs, the concentration of cisplatin peaked within half an hour after a 3-min intravenous infusion of cisplatin (Hellberg et al 2009(Hellberg et al , 2013.…”
Section: Inner Ear Pharmacokineticsmentioning
confidence: 96%
See 2 more Smart Citations